Screening of Trichoderma harzianum against major fungal pathogens of betelvine - BI8EKANANDA MAHANTY; B. DASGUPTA, ALVIRA D'SOUZA, JAYANTA K. ROY, (Indian Phytopathology, 2002)
Eight isolates of Trichoderma ltarzianum Rifai isolated from soils of different betelvine plantations of West Bengal on modified Trichoderma specific medium (TSM). The isolates were studied for their cultural, morphometric characters and antagonistic potential against four major fungal pathogens of betelvine. On PDA, the growth rate of antagonist isolates was quite fast and their cultural morphology was more or less similar. Morphometric studies revealed that length: breadth ratio of phialospores were highest in isolate T3 and that of phialides highest in isolate T 7 • The chlamydospores were found in chains or intercalary or in twins. The antagonistic potential of these isolates of Trichoderma harzianum against four fungal pathogens of betelvine (Phytophthora parasitica Dastur emend Ash., Colletotrichum capsici (Syd.) Butler and Bisby, Sclerotium rolfsii Sacco and Rhizoctonia so/alii Kiihn.) showed that isolates T1 T2 and T3 had highest promise under ill-vitro conditions (dual culture plate technique) by fully overgrowing the pathogens within 5-6 days.